Analisis Butir Soal Penilaian Tengah Semester Mata Pelajaran Bahasa Indonesia - Prawista, Yeni Eka; Rufii, Rufii (MODELING: Jurnal Program Studi PGMI, 2024)
Analysis using SPSS to determine the quality of questions, question validity, reliability, difficulty level, and discriminatory power. Data were obtained from the results of the Mid-Semester Exam of 10th-grade students in Vocational High School using 20 multiple-choice questions. Analysis was conducted using SPSS version 25. From this study, the following results were obtained: (1) 20 questions were deemed valid, (2) 20 questions were considered reliable, (3) in the assessment of the difficulty level, 17 questions were of moderate difficulty, and 3 questions were of easy difficulty, and (4) the quality of questions based on the discriminatory power test revealed 8 questions in the excellent category, 9 questions in the good category, and 3 questions in the moderate category.